Pengaruh Pengendalian Internal, Pemahaman Akuntansi Dan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan UMKM di Kota Bandung - Anbar Shalehah; Astrin Kusumawardani (IKRAITH-EKONOMIKA, 2026)
MSMEs are one of the sectors that contribute to the national economy, but they still face various problems, one of which is related to the quality of financial reports. Quality financial reports are essential as a basis for decision-making and fulfilling obligations to external parties. This study aims to examine the influence of internal control, accounting understanding, and accounting information systems on the quality of MSME financial reports in Bandung City. The research approach used is quantitative with descriptive and verification methods. Data sourced from primary data collected through questionnaires distributed to 96 MSMEs in Bandung City who already have financial reports, with a sampling technique using purposive sampling. Data processing and analysis were carried out using multiple linear regression with the help of SPSS version 26. The results of the study indicate that, partially, internal control does not significantly affect the quality of MSME financial reports. Meanwhile, accounting understanding and accounting information systems have a positive and significant effect on the quality of MSME financial reports. Simultaneously, internal control, accounting understanding, and accounting information systems have a significant effect on the quality of MSME financial reports in Bandung City. The results of this study are expected to be a consideration for MSME actors and related parties in improving the quality of financial reports by increasing accounting understanding and utilizing accounting information systems that are appropriate to the characteristics of MSMEs.